Peran Lembaga Keuangan Syariah dalam Penyerapan Tenaga Kerja di Pulau Sumatera - Dolly Tanzil; Muhammad Bahrul Ulum; Nugraha Pratama (CV. Picmotiv, 2026)
This study aims to analyze the role of financing provided by Islamic financial institutions in labor absorption on Sumatra Island. The research employs a quantitative approach using panel data covering ten provinces in Sumatra Island during the period 2022–2024. The data are obtained from the Financial Services Authority and Statistics Indonesia and analyzed using panel data regression with the Fixed Effect Model. The results show that, simultaneously, financing provided by Islamic Commercial Banks (BUS), Islamic Business Units (UUS), and Islamic Rural Banks (BPRS) has a significant effect on labor absorption. However, partially, only financing from Islamic Business Units (UUS) has a positive and significant effect on labor absorption, while financing from BUS and BPRS shows a positive but insignificant effect. These findings indicate that UUS financing is more effective in promoting job creation due to its strong linkage with the real sector and micro, small, and medium enterprises, which are predominantly labor-intensive.